Effects of repeated high-intensity effort training or repeated sprint training on repeated high-intensity effort ability and in-game performance in professional rugby union players - Glaise, P.; Rogowski, I.; Martin, C. (The Journal of Strength and Conditioning Research, 2024)
This study investigated the effects of repeated high-intensity efforts (RHIE) training compared with repeated sprint exercise (RSE) training on RHIE ability (RHIEa) and in-game performance in professional rugby union players. Thirty-nine, male, professional, rugby union players were randomly assigned to 3 training groups (RHIE training, RSE training, and control). Repeated high-intensity effort ability and high-intensity effort characteristics (including sprints, acceleration, and contact efforts) during official games were measured before and after a 10-week specific (RHIE, RSE, or control) training period. The results of this study showed that concerning RHIEa, both the RHIE and RSE training significantly increased the players' average sprint velocity (p < 0.001, d = -0.39 and p < 0.001, d = -0.53 respectively), average sled push velocity (ASPV; p < 0.001, d = -0.81 and p = 0.017, d = -0.48 respectively), and RHIE score (p < 0.001, d = -0.72 and p < 0.001, d = -0.60 respectively). Repeated high-intensity effort training trended in a smaller increase in average sprint velocity than RSE training, a larger increase in ASPV, and a similar increase in RHIE score. Concerning in-game high-intensity efforts, both the RHIE and RSE training produced significant improvements in the number of sprints (p = 0.047, d = -0.28 and p < 0.001, d = -0.47 respectively), total distance (p < 0.001, d = -0.50 and p = 0.002, d = -0.38 respectively), the number of accelerations (p < 0.001, d = -0.37 and p = 0.003, d = -0.32 respectively), and contact rate (p < 0.001, d = -0.97 and p = 0.020, d = -0.28 respectively). Conversely, the magnitude of the increase in contact rate was almost twice as high in RHIE compared with RSE training. To conclude, the findings of this study were that both RSE and RHIE training are effective methods for developing RHIEa and in-game high-intensity efforts in professional rugby union. In practical applications, as the gains in certain abilities and game performance data differed depending on the training method chosen, we suggest that coaches choose the most appropriate method according to the profile of the players, their position, and the style of play they want to develop.